PENGARUH KOMPENSASI, DISIPLIN KERJA, DAN MOTIVASI TERHADAP PRODUKTIVITAS KARYAWAN DI UD. SURYAFOOD KEDIRI - Sri Astuti, Indah (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
The research was conducted to determine whether employee productivity is determined by compensation, work discipline, and motivation at UD. Suryafood. The method of data collection was obtained through the distribution of questionnaires. The population of this research is 32 employees. The technique used in sampling is saturated sampling technique. Multiple linear regression analysis was used as a technique in data analysis . This study shows that (1) Compensation affects employee productivity with a significance value of 0.003 <0.05, (2) Work discipline affects employee productivity with a significance value of 0.001 <0.05, (3) Motivation affects employee productivity with a value of significance of 0.002 <0.05, (4) Compensation, work discipline, and motivation have a joint effect with a significance value of 0.000 <0.05. The results of the research can be given compensation, work discipline, and motivation on employee productivity at UD. Suryafood.